IS-17 Diagnosing and Managing of Canine Diabetes Mellitus - Maulana Ar Raniri Putra (Hemera Zoa, 2018)
High blood glucose level or hyperglycemia is caused by few factors, such as diabetes mellitus, stress-induced hyperglycemia, use of glucocorticoid, or hyperadrenocorticism. Therefore, it is important to have a thorough examination before having diabetes mellitus as a diagnose from hyperglycemia.Diabetes mellitus happens because of pancreas failure in insulin production that is sufficient to control blood glucose level or insulin failure to decrease blood glucose level because of the insulin resistant. When hyperglycemia happens and over the ability of kidney to absorb glucose then it will appear in the urine (glucosuria). Glucosuria will induce the diuretic-osmotic process that will attract a lot of water to tubulus renalis and induce the clinical sign polyuria. Polyuria will trigger the body to keep hydrated by trigger the thirst center in the brain that cause the clinical sign polydipsia. Insulin is needed by the body to help glucose entering into the cell so it can be used as an energy source. If the insulin level in blood is low then the glucose will fail to enter the cell. This will cause a series of process, the first process is the body will have the energy deficit that trigger the hunger center in the brain to work and cause clinical sign polyphagia. Furthermore, the body will have to break the fat to get energy that can cause weightloss. The use of fat as an energy source continuously will cause high formation of keton bodies that can cause ketoacidosis condition (Ketoacidosis diabetes). Diabetes mellitus consist of 2 types, type 1 and type 2 of diabetes mellitus. Type 1 of diabetes mellitus happens because of the failure of beta cell in insulin production so it produces a very less insulin or none. Dog is an animal that is common to have this type of diabetes mellitus. While type 2 of diabetes mellitus happens because of the insulin failure to work (insulin resistant) which is related to obesity. High level of body fat will induce the release of cytokine that inhibits insulin work so blood glucose level will arise. If this condition runs in a cronic matter then the beta cell will damage and will fail to produce insulin. Cat is a common animal to have this type 2 of diabetes mellitus.